Ultralow-profile high (220) crystal face preferential copper foil surface roughening method
Through the five-step electrolytic copper foil surface roughening method, the problem of taking into account the optimal orientation of the copper foil surface profile and crystal surface in the traditional method is solved, and the high binding force and high-frequency signal transmission performance between the copper foil and the substrate are achieved, meeting the needs of high-speed, high-frequency PCB and high-performance lithium-ion batteries.
Patent Information
- Application Number
- CN202510398772.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-08-05
AI Technical Summary
The traditional electrolytic copper foil surface roughening method is difficult to achieve high (220) crystal surface optimization orientation while reducing the surface profile, resulting in insufficient bonding force between the copper foil and the substrate, which cannot meet the application needs of high-speed, high-frequency PCBs and high-performance lithium-ion batteries.
The five-step surface roughening method is adopted, including degreasing, water washing, pickling activation, primary roughening, curing treatment, secondary roughening and post-treatment. Through specific electrolyte and parameter control, the surface roughness of the copper foil is ensured to be Rz≤2.5μm, and the (220) crystal surface proportion reaches more than 80%.
The bonding force between copper foil and substrate is improved, the attenuation of high-frequency signal transmission is reduced, and the application performance of copper foil in lithium-ion batteries is improved.
Smart Images

Figure CN120425445A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil preparation, and in particular to a method for roughening the surface of an ultra-low profile high (220) crystal plane-preferred copper foil. Background Art
[0002] With the rapid development of the electronic information industry, electrolytic copper foil, a key base material for printed circuit boards (PCBs) and lithium-ion battery electrodes, is facing increasingly stringent performance requirements. In the PCB field, as electronic products move towards miniaturization, lightweighting, and high performance, higher requirements are placed on the surface roughness and crystal orientation of electrolytic copper foil.
[0003] Traditional electrolytic copper foil surface roughening methods struggle to achieve a high (220) preferred orientation while simultaneously reducing the surface profile. This results in insufficient bonding between the copper foil and the substrate, severe signal attenuation during high-frequency signal transmission, and an inability to meet the manufacturing requirements of high-speed, high-frequency PCBs. In the field of lithium-ion batteries, the surface condition of the copper foil also affects battery performance, such as charge and discharge efficiency and cycle life. Therefore, developing a surface roughening method that can achieve ultra-low profile and high (220) preferred orientation has important practical significance and market demand. Summary of the Invention
[0004] The purpose of the present invention is to provide a surface roughening method with ultra-low profile and high (220) crystal plane preference, so as to solve the problem in the prior art that the surface roughening of electrolytic copper foil cannot take into account both low profile and high (220) crystal plane preference orientation, improve the bonding strength between the copper foil and the substrate, reduce the attenuation during high-frequency signal transmission, and at the same time improve the application performance of the copper foil in lithium-ion batteries.
[0005] The present invention provides a method for selectively roughening a surface with an ultra-low profile and a high (220) crystal plane, comprising the following steps:
[0006] Step 1. Pretreatment: Degrease, wash, and pickle the electrolytic copper foil to remove oil, impurities, and the natural oxide layer on the surface, providing a clean, active surface for subsequent roughening. Degreasing is done with an alkaline degreasing agent, soaking for 2-5 minutes at 50-60°C. Rinse with deionized water for 1-2 minutes. Pickling is done with a mixture of sodium persulfate and sulfuric acid at 30-40°C for 1-3 minutes.
[0007] Step 2: Primary roughening: Place the pretreated copper foil in a primary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid for electrolytic roughening. 2+ :20-30g / L, H2SO4:70-80g / L, Cl - :6×10-6 g / L, Ni 2+ :2-5mg / L, citric acid:2-10g / L. During the electrolysis process, the current density is controlled at 20-30A / dm 2 , temperature is 25-35℃, time is 3-4s. Citric acid is an organic acid that helps to adjust the pH value of the electrolyte. It can also form a complex with copper ions, change the deposition process, and promote changes in crystal morphology.
[0008] Step 3, curing treatment: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1-2 minutes; the curing is done with a composition of Cu 2+ :60-80g / L, H2SO4:70-100g / L, Cl - :12×10 - 6 g / L solidification liquid, control the current density to 20-30A / dm 2 , temperature is 50-55℃, and curing time is 3s.
[0009] Step 4, secondary roughening: Place the cured copper foil into a secondary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and lanthanum sulfate for electrolytic roughening. 2+ :20-30g / L, H2SO4:70-80g / L, Cl - :6×10 - 6 g / L, Ni 2+ :2-5mg / L, lanthanum sulfate:5-20mg / L. During the electrolysis process, the current density is controlled at 20-30A / dm 2 , temperature is 25-35℃, time is 3-4s. Lanthanum sulfate as an additive can promote the copper deposition process, make the copper coating more uniform, refine the grains, and improve the microstructure of the copper foil.
[0010] Step 5, Post-treatment: After secondary roughening, the copper foil is washed, subjected to secondary roughening, passivation, and dried. Deionized water is used for rinsing for 1-2 minutes. The secondary roughening method is the same as in step 3. Passivation is performed using a chromate passivation solution, soaking for 30-60 seconds at 30-40°C to improve the copper foil's oxidation resistance. Drying is performed using hot air at 60-80°C for 2-5 minutes.
[0011] The surface roughness of the electrolytic copper foil treated by the above-mentioned surface roughening method is Rz≤2.5μm, the (220) crystal plane accounts for more than 80%, and the peel strength with the substrate reaches more than 1.2N / mm, which effectively meets the application requirements of high-speed, high-frequency PCBs and high-performance lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the technical roadmap of the present invention;
[0013] Figure 2 This is the SEM image of the surface morphology of the copper foil after roughening in Example 1;
[0014] Figure 3 This is the XRD pattern of the crystal plane orientation of the copper foil after roughening in Example 1;
[0015] Figure 4 This is the SEM image of the surface morphology of the copper foil after roughening in Comparative Example 1;
[0016] Figure 5 This is the XRD pattern of the crystal plane orientation of the copper foil after roughening in comparative example 1. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below with reference to the examples, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the scope of protection of the present invention. The process equipment or devices not specifically noted in the following examples are all conventional equipment or devices in the art. Unless otherwise specified, the raw materials used in the examples of the present invention can be obtained commercially; unless otherwise specified, the technical means used in the examples of the present invention are all conventional means well known to those skilled in the art.
[0018] Example 1
[0019] Step 1. Pretreatment: Degrease, rinse, and activate the electrolytic copper foil in sequence to remove oil, impurities, and the natural oxide layer on the surface of the copper foil, providing a clean, active surface for subsequent roughening. Degreasing is done with an alkaline degreasing agent, soaking at 55°C for 5 minutes; rinsing is done with deionized water for 1 minute; and pickling is done with a mixed solution of sodium persulfate and sulfuric acid at 40°C for 3 minutes.
[0020] Step 2: Primary roughening: Place the pretreated copper foil in a primary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid for electrolytic roughening. 2+ :20g / L, H2SO4:70g / L, Cl - :6×10 -6 g / L, Ni 2+ :2mg / L, citric acid:8g / L. During the electrolysis process, the current density was controlled at 25A / dm 2 , temperature is 25℃, time is 4s.
[0021] Step 3, curing treatment: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1-2 minutes; the curing is done with a composition of Cu 2+ :65g / L, H2SO4:70g / L, Cl - :12×10 -6 g / L solidification liquid, and the current density is controlled at 25A / dm 2 , temperature is 55℃ and curing time is 3s.
[0022] Step 4: Secondary roughening: Place the solidified copper foil into a secondary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and lanthanum sulfate for electrolytic roughening. 2+ :20g / L, H2SO4:70g / L, Cl - :6×10 -6 g / L, Ni 2+ :2mg / L, lanthanum sulfate:8mg / L. During the electrolysis process, the current density was controlled at 25A / dm 2 , temperature is 25℃, time is 4s.
[0023] Step 5, Post-treatment: After the secondary roughening, the copper foil is washed, subjected to secondary roughening, passivation, and drying. Deionized water is used for rinsing for 2 minutes. The secondary roughening method is the same as in step 3. Passivation is performed using a chromate passivation solution at 40°C for 60 seconds to improve the copper foil's oxidation resistance. Drying is performed using hot air at 70°C for 5 minutes.
[0024] After testing, the surface roughness of the treated copper foil is Rz = 2.376 μm, the (220) crystal plane accounts for 85.84%, and the peel strength with the substrate reaches 1.731 N / mm.
[0025] Example 2
[0026] Step 1. Pretreatment: Degrease, rinse, and activate the electrolytic copper foil in sequence to remove oil, impurities, and the natural oxide layer on the surface, providing a clean, active surface for subsequent roughening. Degreasing is done with an alkaline degreasing agent, soaking at 60°C for 3 minutes; rinsing is done with deionized water for 1 minute; and pickling is done with a mixed solution of sodium persulfate and sulfuric acid at 40°C for 2 minutes.
[0027] Step 2: Primary roughening: Place the pretreated copper foil in a primary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid for electrolytic roughening. 2+ :25g / L, H2SO4:75g / L, Cl - :6×10-6 g / L, Ni 2+ :3mg / L, citric acid:5g / L. During the electrolysis process, the current density was controlled at 20A / dm 2 , temperature is 30℃, time is 3s.
[0028] Step 3, curing treatment: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1-2 minutes; the curing is done with a composition of Cu 2+ :60g / L, H2SO4:80g / L, Cl - :12×10 -6 g / L solidification liquid, and the current density is controlled to be 20A / dm 2 , temperature is 50℃ and curing time is 3s.
[0029] Step 4: Secondary roughening: Place the solidified copper foil into a secondary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and lanthanum sulfate for electrolytic roughening. 2+ :25g / L, H2SO4:75g / L, Cl - :6×10 -6 g / L, Ni 2+ :3mg / L, lanthanum sulfate:5mg / L. During the electrolysis process, the current density was controlled at 20A / dm 2 , temperature is 30℃, time is 3s.
[0030] Step 5, Post-treatment: After the secondary roughening, the copper foil is washed, subjected to secondary roughening, passivation, and drying. Deionized water is used for rinsing for 2 minutes. The secondary roughening method is the same as in step 3. Passivation is performed using a chromate passivation solution, soaking for 30 seconds at 40°C to improve the copper foil's oxidation resistance. Drying is performed using hot air at 80°C for 2 minutes.
[0031] After testing, the surface roughness Rz of the treated copper foil was 2.399 μm, the (220) crystal plane accounted for 82.39%, and the peel strength with the substrate reached 1.545 N / mm.
[0032] Example 3
[0033] Step 1. Pretreatment: Degrease, rinse, and activate the electrolytic copper foil in sequence to remove oil, impurities, and the natural oxide layer on the surface of the copper foil, providing a clean and active surface for subsequent roughening. Degreasing is done with an alkaline degreasing agent, soaking at 50°C for 5 minutes; rinsing is done with deionized water for 2 minutes; and pickling is done with a mixed solution of sodium persulfate and sulfuric acid at 30°C for 3 minutes.
[0034] Step 2: Primary roughening: Place the pretreated copper foil in a primary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid for electrolytic roughening. 2+ :30g / L, H2SO4:80g / L, Cl - :6×10 -6 g / L, Ni 2+ :5mg / L, citric acid:10g / L. During the electrolysis process, the current density was controlled at 30A / dm 2 , temperature is 35℃, time is 3s.
[0035] Step 3, curing treatment: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1-2 minutes; the curing is done with a composition of Cu 2+ :80g / L, H2SO4:100g / L, Cl - :12×10 -6 g / L solidification liquid, and the current density is controlled to be 30A / dm 2 , temperature is 53℃ and curing time is 3s.
[0036] Step 4: Secondary roughening: Place the solidified copper foil into a secondary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and lanthanum sulfate for electrolytic roughening. 2+ :30g / L, H2SO4:80g / L, Cl - :6×10 -6 g / L, Ni 2+ :5mg / L, lanthanum sulfate:15mg / L. During the electrolysis process, the current density was controlled at 30A / dm 2 , temperature is 35℃, time is 3s.
[0037] Step 5, Post-treatment: After the secondary roughening, the copper foil is washed, subjected to secondary roughening, passivation, and drying. Deionized water is used for rinsing for 2 minutes. The secondary roughening method is the same as in step 3. Passivation is performed using a chromate passivation solution at 40°C for 30 seconds to improve the copper foil's oxidation resistance. Drying is performed using hot air at 70°C for 4 minutes.
[0038] After testing, the surface roughness Rz of the treated copper foil was 2.463 μm, the (220) crystal plane accounted for 83.72%, and the peel strength with the substrate reached 1.581 N / mm.
[0039] Comparative Example 1
[0040] Step 1. Pretreatment: Degrease, rinse, and activate the electrolytic copper foil in sequence to remove oil, impurities, and the natural oxide layer on the surface of the copper foil, providing a clean, active surface for subsequent roughening. Degreasing is done with an alkaline degreasing agent, soaking at 50°C for 5 minutes; rinsing is done with deionized water for 1 minute; and pickling is done with a mixed solution of sodium persulfate and sulfuric acid at 30°C for 3 minutes.
[0041] Step 2: Primary roughening: Place the pretreated copper foil in a primary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid for electrolytic roughening. 2+ :20g / L, H2SO4:70g / L, Cl - :6×10 -6 g / L, Ni 2+ :2mg / L. During the electrolysis process, the current density was controlled at 20A / dm 2 , temperature is 25℃, time is 4s.
[0042] Step 3, curing treatment: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1 minute; the curing is done with a composition of Cu 2+ :65g / L, H2SO4:70g / L, Cl - :12×10 -6 g / L solidification liquid, and the current density is controlled to be 20A / dm 2 , temperature is 55℃ and curing time is 3s.
[0043] Step 4: Secondary roughening: Place the solidified copper foil into a secondary roughening electrolyte containing copper sulfate, sulfuric acid, copper chloride, nickel sulfate and lanthanum sulfate for electrolytic roughening. 2+ :20g / L, H2SO4:70g / L, Cl - :6×10 -6 g / L, Ni 2+ :2-5mg / L. During the electrolysis process, the current density is controlled at 20A / dm 2 , temperature is 25℃, time is 4s.
[0044] Step 5, Post-treatment: After the secondary roughening, the copper foil is washed, subjected to secondary roughening, passivation, and drying. Deionized water is used for rinsing for 2 minutes. The secondary roughening method is the same as in Step 3. Passivation is performed using a chromate passivation solution at 30°C for 60 seconds to improve the copper foil's oxidation resistance. Drying is performed using hot air at 60°C for 5 minutes.
[0045] After testing, the surface roughness Rz of the treated copper foil was 3.154μm, the (220) crystal plane accounted for 42.79%, and the peel strength with the substrate reached 1.262N / mm.
Claims
1. A method for surface roughening of electrolytic copper foil with ultra-low profile and high (220) crystal plane preference, characterized in that: The following steps are involved: Pretreatment step: The electrolytic copper foil is sequentially subjected to degreasing, water washing and pickling activation treatment. The degreasing treatment uses an alkaline degreasing agent and is immersed at a temperature of 50-60°C for 2-5 minutes; the water washing uses deionized water and the rinsing time is 1-2 minutes; the pickling treatment uses a mixed solution of sodium persulfate and sulfuric acid and is treated at a temperature of 30-40°C for 1-3 minutes; Primary roughening step: The pretreated copper foil is placed in a primary roughening electrolyte for electrolytic roughening, wherein the primary roughening electrolyte contains copper sulfate, sulfuric acid, copper chloride, nickel sulfate and citric acid, wherein Cu 2+ The concentration is 20-30g / L, the concentration of H2SO4 is 70-80g / L, and the concentration of Cl - The concentration is 6×10 -6 g / L, Ni 2+ The concentration is 2-5 mg / L, the concentration of citric acid is 2-10 g / L; during the electrolysis process, the current density is controlled at 20-30 A / dm 2 , temperature is 25-35℃, time is 3-4s. Curing treatment step: After the first roughening, the copper foil is washed and cured. The washing is done with deionized water for 1-2 minutes. The curing liquid composition of the curing treatment is Cu 2+ The concentration is 60-80g / L, the concentration of H2SO4 is 70-100g / L, and the concentration of Cl - The concentration is 12×10 -6 g / L, and the current density is controlled at 20-30A / dm 2 , temperature is 50-55℃, curing time is 3s; Secondary roughening step: Place the cured copper foil in a secondary roughening electrolyte for electrolytic roughening. The secondary roughening electrolyte contains copper sulfate, sulfuric acid, copper chloride, nickel sulfate, and lanthanum sulfate. 2+ The concentration is 20-30g / L, the concentration of H2SO4 is 70-80g / L, and the concentration of Cl - The concentration is 6×10 -6 g / L, Ni 2+ The concentration is 2-5 mg / L, the concentration of lanthanum sulfate is 5-20 mg / L; during the electrolysis process, the current density is controlled at 20-30 A / dm 2 , temperature is 25-35℃, time is 3-4s; Post-processing steps: After the secondary roughening, the copper foil is washed, secondary cured, passivated and dried. The washing adopts deionized water and the rinsing time is 1-2 minutes. The secondary curing method is the same as the curing treatment in the curing treatment step. The passivation treatment adopts chromate passivation solution and is immersed at a temperature of 30-40°C for 30-60s. The drying treatment adopts hot air drying at a temperature of 60-80°C and a time of 2-5 minutes.
2. The method for surface roughening of electrolytic copper foil with ultra-low profile and high (220) crystal plane preference according to claim 1, characterized in that: The alkaline degreasing agent is a mixed solution containing sodium hydroxide, sodium carbonate and a surfactant.
3. The method for surface roughening of electrolytic copper foil with ultra-low profile and high (220) crystal plane preference according to claim 1, characterized in that: In the mixed solution of sodium persulfate and sulfuric acid, the concentration of sodium persulfate is 5-15 g / L, and the concentration of sulfuric acid is 10-20 g / L.
4. The method for surface roughening of electrolytic copper foil with ultra-low profile and high (220) crystal plane preference according to claim 1, characterized in that: In the primary roughening step and the secondary roughening step, the electrolyte is stirred by circulating a micro self-priming water pump.
5. The electrolytic copper foil prepared by the method for surface roughening of electrolytic copper foil with ultra-low profile and high (220) crystal plane preference according to claim 1 is characterized in that: The surface roughness of the electrolytic copper foil is Rz≤2.5 μm, the (220) crystal plane accounts for more than 80%, and the peeling strength with the substrate reaches more than 1.2 N / mm.